Learning Approaches for Entrepreneurship Education - Hamburg, Ileana (Archives of Business Research, 2015)
Entrepreneurship education is one important topic for all European countries preparing people who can contributes to the ability of an economy to innovate, to create new businesses and new ideas. In both higher education as well as in vocational education and training (VET), suitable learning methods, special education modules oriented to entrepreneurial competences including traversal skills and attitudes as well as more specialized knowledge and business skills are necessary and could be supported by mentors. More options and opportunities for European and international exchanges are necessary. This paper will give information about entrepreneurship education, mentoring and suitable learning methods for entrepreneurs, particularly problem based learning – PBL, conclusions and recommendations. Keywords: entrepreneurship education, diversity, mentoring, problem based learning